Democratic transit in terms of security and development: Ukrainian and foreign experience : collective monograph - Кормич, Людмила Іванівна; Кормич, Л. І.; Kormych, Liudmyla I.; Кормич, Анатолій Іванович; Кормич, А. І.; Kormych, Anatolii I.; Краснопольська, Тетяна Миколаївна; Краснопольська, Т. М.; Krasnopolska, Тetiana М.; Завгородня, Юлія Володимирівна; Завгородня, Ю. В.; Zavhorodnia, Yuliia V.; et al. (Lviv-Toruń : Liha-Pres, 2019)
The monograph reveals the multifaceted and multidimensional process of democratic transit. The specific sections focus on the priority problems of modern democracy. Creating a secure space for the existence and development of states is analyzed as a guarantee of the success of democratic transformations. The essence of security in the context of the hybrid nature of political processes is characterized. The specifics of conflicts in the modern world are highlighted. The peculiarities inherent in the legal, political, cultural, ethno-national dimensions of democratic transit are investigated. The basic signs of democratization on the examples of Ukraine and some foreign countries are clarified.
Democratic transit in terms of security and development: Ukrainian and foreign experience : collective monograph / L. І. Kormych, А. І. Kormych, T. M. Krasnopolska, Yu. V. Zavgorodnya, etc.; ed. by L. I. Kormych. – Lviv-Toruń : Liha-Pres, 2019. – 296 p. URL: https://hdl.handle.net/11300/28522
Keywords: democratic transit; modern democracy; democratic transformations; political processes; democratization; демократичний транзит; сучасна демократія; демократичні перетворення; політичні процеси; демократизація